INOVASI KURIKULUM DAN PENERAPAN KURIKULUM 2013 DI MASA PANDEMI COVID19 - Ahmad Ridwan; Muhaimin Bahta; Fathul Fauzi (ICO EDUSHA, 2021)
Curriculum is very important because it is one of the most important elements in educational development and social change. In addition, Indonesia has undergone extensive changes in the world's economy in Indonesia. Where kurilkulum 2013 is now in need of an evaluation and innovation to promote education in the future. This article described 1. Curriculum 2013 phase 2 update. How does the 2013 curriculum apply during During this pandemic in Indonesia . Articles methods use methodology, and are aided by data collection techniques through observation, interviews and documentation then in analysis and verification of data. Found in the article are the 2013 curriculum innovation and application of the 2013 curriculum in this pandemic. So that it can create innovation Good curriculum. Keywords: Curriculum Innovation, 2013 Curriculum Implementation, Covid19 Pandemic References “3620-Article Text-10048-1-10-20200503.Pdf,” n.d. “4335-Article Text-12470-1-10-20211008.Pdf,” n.d. Amiruddin, Amiruddin, Irma Rubianti, Nikman Azmin, Muh Nasir, and Ahmad Sandi. “Analisis Penerapan Kurikulum 2013 Dalam Meningkatkan Kualitas Pembelajaran Masa Pandemik Covid-19 di SMAN 3 Kota Bima.” Jurnal Ilmiah Mandala Education 7, no. 4 (October 11, 2021). https://doi.org/10.36312/jime.v7i4.2398. Bahri, Syamsul. “PENGEMBANGAN KURIKULUM DASAR DAN TUJUANNYA.” Jurnal Ilmiah Islam Futura 11, no. 1 (February 3, 2017): 15. https://doi.org/10.22373/jiif.v11i1.61. “BUKU_INOVASI_PENDIDIKAN20200426-94217-1xn5kij-with-Cover-Page-v2.Pdf,” n.d. Damai, I Wayan. “Inovasi Pembelajaran E-Learning Matematik Melalui Flatform Era Covid 19,” 1 (2021): 13. Fatimah, Ima Frima, Rida Nurfarida, Agus Salim Mansyur, and Qiqi Yuliati Zaqiah. “STRATEGI INOVASI KURIKULUM; SEBUAH TINJAUAN TEORETIS,” n.d., 15. Mustafa, Pinton Setya, and Wasis Djoko Dwiyogo. “Kurikulum Pendidikan Jasmani, Olahraga, dan Kesehatan di Indonesia Abad 21.” JARTIKA Jurnal Riset Teknologi dan Inovasi Pendidikan 3, no. 2 (July 11, 2020): 422–38. https://doi.org/10.36765/jartika.v3i2.268. Rusdiana, Dr H A. “KONSEP INOVASI PENDIDIKAN,” n.d., 127. Utomo, Sigit Tri. “INOVASI KURIKULUM DALAM DIMENSI TAHAPAN PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM.” Journal of Research and Thought on Islamic Education (JRTIE) 3, no. 1 (April 30, 2020): 19–38. https://doi.org/10.24260/jrtie.v3i1.1570. Yasir, Saddan Yasir, Hamidah Hamidah, and Putri Dewi Anggia. “PENERAPAN KURIKULUM 2013 PADA MASA PANDEMI COVID-19 DI SMP IT AD-DURRAH MEDAN.” Ilmuna: Jurnal Studi Pendidikan Agama Islam 3, no. 1 (March 25, 2021): 14-28 https://doi.org/10.54437/ilmuna.v3i1.189. Zahrawati, Fawziah. “Penerapan Pembelajaran Daring dengan Kurikulum 2013 pada Masa Pandemik COVID-19 di SMA Negeri 1 Nunukan” 15 (2021): 11.